Hubungan Motivasi Kerja Dengan Pelaksanaan Pendokumentasian Proses Keperawatan Di Rumah Sakit Siti Aisyah Lubuklinggau Tahun 2025 - Wenny Adriyanti; Emi Pebriani; Nuche Marlianto (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Documentation of nursing care plays an important role in responding to theincreasingly critical demands of the community regarding their rights to health services. Therefore, hospitals as health units must provide the best service to patients in order to maintain the quality of health services in hospitals, one of which is by paying attention to compliance in documenting the nursing care process. The purpose of this study was to determine the relationship between work motivation and the implementation of nursing process documentation at Siti Aisyah Hospital in Lubuklinggau in 2025. The research method used was descriptive quantitative research with a cross-sectional approach. The sampling technique used was total sampling with a sample size of 66 people. The results of the univariate analysis showed that most respondents (34.8%) had low motivation, while a small number of respondents (22.7%) had incomplete documentation. The results of the bivariate analysis of work motivation and the implementation of nursing process documentation (0.000). There is a relationship between work motivation and the implementation of nursing process documentation at Siti Aisyah Hospital in Lubuklinggau in 2025. Respondents are expected to maintain and improve the quality of documentation by following applicable procedures and maintaining their enthusiasm for work despite facing challenges in carrying out their duties.